Biodiesel Production From Algae to Overcome the Energy Crisis - Suliman Khan; Rabeea Siddique; Wasim Sajjad; Ghulam Nabi; Khizar Mian Hayat; Pengfei Duan; Lunguang Yao (Bogor Agricultural University, Indonesia, 2017)
The use of energy sources has reached at the level that whole world is relying on it. Being the major source of energy, fuels are considered the most important. The fear of diminishing the available sources thirst towards biofuel production has increased during last decades. Considering the food problems, algae gain the most attention to be used as biofuel producers. The use of crop and food-producing plants will never be a best fit into the priorities for biofuel production as they will disturb the food needs. Different types of algae having the different production abilities. Normally algae have 20%–80% oil contents that could be converted into different types of fuels such as kerosene oil and biodiesel. The diesel production from algae is economical and easy. Different species such as tribonema, ulothrix and euglena have good potential for biodiesel production. Gene technology can be used to enhance the production of oil and biodiesel contents and stability of algae. By increasing the genetic expressions, we can find the ways to achieve the required biofuel amounts easily and continuously to overcome the fuels deficiency. The present review article focusses on the role of algae as a possible substitute for fossil fuel as an ideal biofuel reactant.